2002
DOI: 10.1366/000370202760355316
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Sorting of Wood Treated with Chromated Copper Arsenate Using Laser-Induced Breakdown Spectroscopy

Abstract: This paper details the design, implementation, and field evaluation of an online detector system using laser-induced breakdown spectroscopy (LIBS) for the analysis of copper chromated arsenate (CCA) treated wood products. The LIBS-based instrument functioned by creating the laser-induced plasma directly on the sample surface while wood was translated under the detector system, and was successful in discriminating between CCA treated wood and untreated wood products based on the atomic emission signal of chromi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(18 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…LIBS is an emerging technology for real-time chemical analysis that has found application in a variety of industrial [1][2][3][4][5], cultural [6][7] and security [8][9][10][11] applications and presently is under development for extraterrestrial exploration [12][13][14]. Over the past two decades, there have been a variety of applications of LIBS to geological materials, mostly focused on quantitative determination of a few elements [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…LIBS is an emerging technology for real-time chemical analysis that has found application in a variety of industrial [1][2][3][4][5], cultural [6][7] and security [8][9][10][11] applications and presently is under development for extraterrestrial exploration [12][13][14]. Over the past two decades, there have been a variety of applications of LIBS to geological materials, mostly focused on quantitative determination of a few elements [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Another application that is of great interest to plant and forestry scientists is the chemistry of wood response to precipitation and forest fires that occur naturally in the environment or controlled fire events. The housing industry is very much interested in sorting preservative treated wood [21,[60][61][62]. The authors have shown that LIBS has practical applications in recycling facilities and on building sites.…”
Section: Biological Applications Of Libsmentioning
confidence: 99%
“…Other newer developments concentrate on sophisticated techniques for sorting the contaminated material from acceptable wood waste. X-ray fluorescence spectroscopy (XFR) and laser-induced breakdown spectroscopy (LIBS) are promising detector technologies to identify CCA (chromated copperarsenate)-treated wood and CCA-containing paints on wood, and also other types of preservatives (Peek 1998, Peylo & Peek 1998, Uhl et al 2001, Blassino et al 2002, Moskal & Hahn 2002, Solo-Gabriele et al 2004, Block et al 2007, Dubey et al 2007). …”
Section: Risk Assessment Of Wood Materialsmentioning
confidence: 99%